CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.